School psychology in Zimbabwe - Mpofu, E.; Mutepfa, M.M.; Chireshe, R.; Kasayira, Joseph M. (Sage Publications, 2021)
The term educational psychologist, not school psychologist, is used in Zimbabwe. Thus, the terms school psychology and school psychologist, as used in this chapter, refer to educational psychology and educational psychologist, as used in Zimbabwe. This chapter looks at the status of school psychology in Zimbabwe as viewed through the following topics: The Context of School Psychology; Origin, History, and Current Status of School Psychology; Infrastructure of School Psychology; Preparation of School Psychologists; Roles, Functions, and Responsibilities of School Psychologists; and Current Issues Impacting School Psychology. School psychologists face several challenges to the development and provision of services. These challenges include underfunding by the central government, high job attrition, and the consequent erosion of the quality of training. Diminished financial resources result from a decision by the central government to not assume the financial responsibilities that formerly were provided by the Swedish International Development Agency. A possible solution to the problem of resource insufficiency is to levy service fees to people in middle to high income brackets whose students receive school psychological services and to provide school psychology services at no cost only to students from families who fall below a means test. The availability of resources for school psychologists to carry out their job functions and a quadrupling of the number of school psychologists per region would reduce job attrition due to frustrations associated with resource scarcity and case overload. Attrition to private sector employment opportunities is unlikely to be remedied soon. Many Zimbabwean students with disabilities and their families are unaware of the availability of school psychology services and the type or relevance of the services (Mpofu, Zindi, Oakland, & Peresuh, 1997). Creating awareness among the general public and some schools as to the availability and quality of school psychological services constitutes a long-standing problem. Among the major issues for research by school psychologists is the practice of culturally sensitive school psychology (Mpofu, 2003; Mpofu et al., 2005). The development of valid assessment procedures for students receiving school psychological services is urgently needed. Zimbabwe's school psychological services are probably some of the most advanced on the African continent, and the work of school psychologists in Zimbabwe has developed appreciably over the past three decades. The potential for school psychology in Zimbabwe is great, dependent on improved managerial functions, increased support by the central government, and application of contextually relevant research to guide practice.